A Century of World Conferences on Faith and Order - Mateus, Odair Pedroso (The ecumenical review, 2023)
In February 2022, the central committee of the World Council of Churches (WCC) agreed the proposal for a World Conference on Faith and Order to be held in 2025 to coincide with the 1700th anniversary of the Council of Nicaea. This will be the sixth such world conference since the First World Conference on Faith and Order was held in 1927 in Lausanne, Switzerland. Against this background, this article reviews the history of the World Conferences on Faith and Order from the origins of the Faith and Order movement to the Fifth World Conference on Faith and Order in 1993. Although created autonomous and self-governing, organized around regular world conferences, with the creation of the WCC in 1948, the Faith and Order movement became a commission of the WCC.